Regular Associated Solution Model for the Estimation of Free Energy of Mixing of Binary Liquid Alloys - Adhikari, D; Singh, BP; Jha, IS (Scientific World, 2010)
We have found the equilibrium constants and pairwise interaction energies between the species and the complexes of liquid CuSn, AgAl, FeSi, CdNa and HgNa alloys on the basis of regular associated solution model. These parameters are then used to estimate the free energies of mixing of each alloy. The observed asymmetry in the free energy of mixing of each alloy with respect to concentration is well explained. Key Words: Free energy of mixing; Asymmetry; Binary alloys; Interaction energy. DOI: 10.3126/sw.v8i8.3842 Scientific World Vol.8(8) 2010 pp.30-33